Comparison of inflammatory markers (Interleukin-1?, Interleukin-6 and hs-CRP) in Type 2 Diabetes Mellitus patients with and without Nephropathy: A hospital based cross-sectional study in Mumbai - Pooja A Baviskar; Vinayak W Patil; Tushar.R.Bagle (Global Journal of Medicine and Public Health, 2024)
Background Diabetic nephropathy is a microvascular diabetic complication secondary to longstanding diabetes due to angiopathy of capillaries in glomeruli now recognized as long standing chronic inflammatory disease. The study was done with an objective to compare the levels of inflammatory biomarkers (hs-CRP,IL-1?,IL-6) in patients of type 2 diabetes mellitus with nephropathy and without nephropathy.